Ultrasound-assisted dispersive liquid–liquid microextraction of tetracycline drugs from egg supplements before flow injection analysis coupled to a liquid waveguide capillary cell - Rodríguez, Michael Pérez [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Springer Nature, 2016)
A simple, rapid, and efficient ultrasound-assisted dispersive liquid–liquid microextraction (US-DLLME) method was developed for extraction of tetracycline residues from egg supplement samples, with subsequent determination by flow injection analysis (FIA) coupled to a liquid waveguide capillary cell (LWCC) and a controlled temperature heating bath. Tetracyclines react with diazotized p-sulfanilic acid, in a slightly alkaline medium, to form azo compounds that can be measured at 435 nm. The reaction sensitivity improved substantially (5.12-fold) using an in-line heating temperature of 45 °C. Multivariate methodology was used to optimize the factors affecting the extraction efficiency, considering the volumes of extraction and disperser solvents, sonication time, extraction time, and centrifugation time. Good linearity in the range 30–600 μg L−1 was obtained for all the tetracyclines, with regression coefficients (r) higher than 0.9974. The limits of detection ranged from 6.4 to 11.1 μg L−1, and the recoveries were in the range 85.7–96.4 %, with relative standard deviation lower than 9.8 %. Analyte recovery was improved by approximately 6 % when the microextraction was assisted by ultrasound. The results obtained with the proposed US-DLLME-FIA method were confirmed by a reference HPLC method and showed that the egg supplement samples analyzed were suitable for human consumption.
Keywords: Egg supplements; Flow injection analysis (FIA); Liquid waveguide capillary cell (LWCC); Tetracyclines; Ultrasound-assisted dispersive liquid–liquid microextraction (US-DLLME)